Comparison of the melt memory effects in matched fractions segregated from Ziegler-Natta and metallocene-made isotactic polypropylene with similar total defect content. (16th September 2021) - Wang, Xinxin; Yi, Jianjun; Wang, Li; Feng, Jiachun
Abstract: It was well known that the defects in the polymer chains could significantly influence the crystallization process of semi-crystalline polymers. In this work, the role of defect distribution in the melt memory effects was studied by comparatively investigating a pair of Ziegler-Natta and metallocene-made isotactic polypropylene (ZN-iPP and M-iPP) fraction specimens with the same total defect content which were obtained from two raw parent samples through the solvent extraction. The characterization results of melting behaviors, polymorphic structures, and the successive self-nucleation and annealing analysis demonstrated that these two fractions exhibited the different distribution of defects, i.e., the defect distribution in the M-iPP specimen was random while that in the ZN-iPP specimen was nonstatistical. The results of self-nucleation (SN) experiments indicated that the M-iPP exhibited much wider temperature range of Domain II than the ZN-iPP with similar total defect content, which indicated that the M-iPP showed a much stronger melt memory effect. Considering the effect of the microstructure on the crystallization behavior and the sequences containing defects could be excluded from the crystalline regions during the formation of crystal, we speculated that the random distributed defects in M-iPP could form a continuous interface between the crystalline regions and amorphous phase which could cause a heterogeneous melt and strengthen the melt memory effect. Graphical abstract: Image 1 Highlights: Defect distribution influenced the melt memory effect of iPP. The defect in M-iPP was random while that was nonstatistical in ZN-iPP. The M-iPP with random distributed defects exhibited stronger melt memory effect.